From solid waste to a high-performance Li3.25Si anode: towards high initial Coulombic efficiency Li–Si alloy electrodes for Li-ion batteries. (20th July 2022) - He, Yayue; Zhang, Youjia; Li, Zhenxi; Cao, Peng-Fei; Yang, Huabin; Gao, Shilun
Abstract : With solid wastes as precursors, Li3.25 Si was fabricated as an anode, combining the advantages of low-cost and high initial Coulombic efficiency. Abstract : As a promising anode material for next-generation high-energy density lithium-ion batteries (LIBs), one of the main technical issues for silicon (Si) electrodes is the low initial Coulombic efficiency (ICE). By a pre-lithiation process, preparation of lithium–silicon (Li–Si) alloy electrodes can efficiently improve the ICE, thus leading to excellent electrochemical performance. Herein, with solid wastes as precursors, we report a cost-efficient approach for the fabrication of Li3.25 Si anode materials via simple magnesiothermic reduction and then mechanical alloy reaction methods, combining the advantages of low-cost and high ICE. The prepared Li3.25 Si@acetylene black (Li3.25 Si@A) electrode exhibits excellent electrochemical performance with a high reversible capacity of 1138.9 mA h g −1 over 90 cycles at a current density of 100 mA g −1 and its ICE is as high as 107.7%, which is superior to that of the commercial Li3.25 Si@A electrode. With a simple and low-cost manufacturing process and high ICE, the fabrication process will be definitely meaningful in achieving low-cost and high-capacity anode materials with a prolonged cycle life.